Spain : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Spanish economy suffered an unprecedented double-dip recession with the rising unemployment and public debt situation. Spain also suffered a reversal of private external financing flows in 2011 and 2012. To counter this situation, major policy actions have been taken in the banking sector. The fiscal framework has been improved, and a scheme for clearing subnational arrears has been established. The Executive Board emphasized the need for sustained efforts and a medium-term strategy for structural reforms and financial sector restructuring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet